Puccini's Tosca - Illica, Luigi, 1857-1919.; Fisher, Burton D.; Giacosa, Giuseppe, 1847-1906.; Illica, Luigi, 1857-1919.; Illica, Luigi, 1857-1919.; Puccini, Giacomo, 1858-1924.; Sardou, Victorien, 1831-1908. (Miami, Fla. : Opera Journeys Pub., 2005)
A comprehensive guide to Puccini's TOSCA, featuring insightful and in depth Commentary and Analysis, a complete, newly translated Libretto with Italian/English side-by side, and over 20 music highlight examples.
Tosca / Opera Classics Library Series; Title Page; Dedication; Contents; a Prelude; Provenance; Commentary and Analysis; Principal Characters in Tosca; Brief Story Synopsis; Story Narrative with Music Highlights; Libretto; Discography; Videography; Dictionary of Opera and Musical Terms.
Based on: La Tosca / Victorien Sardou.
Libretto by Giuseppe Giacosa and Luigi Illica.
Text in English; libretto in English and Italian.
Includes discography and videography.
eBooks on EBSCOhost
Keywords: Puccini, Giacomo, -- 1858-1924.; Tosca (Puccini, Giacomo); Operas -- Librettos; Opéras -- Livrets; MUSIC -- Genres & Styles -- Opera; Operas -- Librettos